HAK KEKAYAAN INTELEKTUAL PADA PENDIDIKAN TINGGI JARAK JAUH - Nurhayati, Ratna (LPPM Universitas Terbuka, 2007)
This article discusses an Intellectual Property Rights system, especially for the benefit of the distance education researchers. In doing research, researchers have to extort their mind, creativity and intellectual ability to yield something. As the only distance education institution in Indonesia, various development products for the interest of the learning process have been developed by Universitas Terbuka. Therefore, the research findings need to be protected by the Intellectual Property Rights. What we need to do now is to manage those research outcomes regarded as the precious asset of Intellectual Properties owned by Universitas Terbuka